Personal Branding Selebtwit Takdir Ridwan (@jek___) di Media Sosial Twitter - Sukma, Unzila Yuniar; Gelgel, Ni Made Ras Amanda; Suryawati, I Gusti Agung Alit (E-Jurnal Medium; Vol 3 No 1 (2022): Jurnal Ilmu Komunikasi Vol 3 No 1 Tahun 2022, 2022)
Twitter is a very popular platform that can be used to build personal branding as it is interactive and spreads by word of mouth. Takdir Ridwan or most-known by Jek (@jek___) is one of the Twitter celebrity who actively uses Twitter to facilitate two-way communication with his followers by bringing his own characteristics. This study uses a qualitative descriptive approach that aims to explain the personal branding strategies used by Jek through his tweets on Twitter by using Freddy Rangkuti's main concept named Personal Branding Pyramid. This study shows that Jek has his own personal branding as humorous priest and has 5 uniqueness. Also, this study shows that Jek already fulfill the four stages of the Personal Branding Pyramid. Keywords : Personal Branding, Personal Branding Pyramid, Twitter Celebrity